Optimization of a method for the simultaneous determination of free glycerine, monoglycerides, diglycerides, triglycerides in biodiesel by GC/FID using the deviating agent BSTFA/TMCS - Hương, Lê Thị Thanh; Hoa, Vũ Thị (Vietnam Journal of Chemistry, 2014)
This study proposes a new method for the simultaneous determination of free glycerin, monoglycerides, diglycerides and triglycerides in biodiesel by GC/FID using the derivating agent N,O−bis (trimethylsilyl)trifluoracetamide (BSTFA) and the only internal standard (n–tetradecane). The silylation reaction was optimized. The sensitivity, precision and repeatability of method were evaluated.